Finding the missing link: examining the mediating role of sustainable public procurement behaviour - Grandia, Jolien (Journal of cleaner production, 2016)
Governments use sustainable public procurement to reduce the negative aspects of production and consumption. The more sustainable the goods and services that the government buys are, the greater the impact on the market and the environment. However, studies show that the degree of sustainable procurement is not constant within a public organization, but varies across procurement projects. Studies into sustainable public procurement identify several organizational factors that drive or hinder the implementation of sustainable (public) procurement. However these studies have not yet examined how these factors influence the implementation and thus degree of sustainable public procurement. This paper tries to fill that gap and tests whether behaviour acts as a mediator between knowledge, commitment to change, and the application of sustainable procurement in procurement projects in the Dutch national government. To test our hypotheses a survey was held amongst public procurers working in the Dutch national government. The results show that sustainable procurement behaviour positively mediates the relationship between on the one hand affective commitment to change and knowledge, and on the other hand the application of both compulsory and voluntary sustainable public procurement in procurement projects. Especially voluntary sustainable procurement proved receptive for knowledge and affective commitment to change. It is therefore concluded that to increase the application of sustainable procurement public organisations should focus on increasing knowledge about sustainability and the environment, affective commitment to change and sustainable procurement behaviour.